12-(3x-7)=2x-(x-1)

Simple and best practice solution for 12-(3x-7)=2x-(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12-(3x-7)=2x-(x-1) equation:


Simplifying
12 + -1(3x + -7) = 2x + -1(x + -1)

Reorder the terms:
12 + -1(-7 + 3x) = 2x + -1(x + -1)
12 + (-7 * -1 + 3x * -1) = 2x + -1(x + -1)
12 + (7 + -3x) = 2x + -1(x + -1)

Combine like terms: 12 + 7 = 19
19 + -3x = 2x + -1(x + -1)

Reorder the terms:
19 + -3x = 2x + -1(-1 + x)
19 + -3x = 2x + (-1 * -1 + x * -1)
19 + -3x = 2x + (1 + -1x)

Reorder the terms:
19 + -3x = 1 + 2x + -1x

Combine like terms: 2x + -1x = 1x
19 + -3x = 1 + 1x

Solving
19 + -3x = 1 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
19 + -3x + -1x = 1 + 1x + -1x

Combine like terms: -3x + -1x = -4x
19 + -4x = 1 + 1x + -1x

Combine like terms: 1x + -1x = 0
19 + -4x = 1 + 0
19 + -4x = 1

Add '-19' to each side of the equation.
19 + -19 + -4x = 1 + -19

Combine like terms: 19 + -19 = 0
0 + -4x = 1 + -19
-4x = 1 + -19

Combine like terms: 1 + -19 = -18
-4x = -18

Divide each side by '-4'.
x = 4.5

Simplifying
x = 4.5

See similar equations:

| -7(x+5)+3(x-6)= | | f-1(2)= | | 5-(8-x)=3-(x-6) | | -(v-2)=-4(v-8)-8v | | x(x+3)=-8 | | (2x^2)+5x+8=0 | | 16z=-128 | | 7-q-q-2q=80 | | 4p-25=-32+5p | | 4p-12=-3+p | | -7x-10x=-85 | | 4x-10x=70 | | -5x-15=-95 | | -60=3+9x | | (3x^2)-5x-7=0 | | (2x^2)+8x=0 | | 1+x^2=0 | | (2x^2)-7x-1=0 | | 27a^3x^4-8x=0 | | 8+2x=x+40 | | 3y+24+6-2=33 | | -28+4=0 | | ln(x+1)ln(x)+ln(x^2)=1 | | ln(x+a)ln(x)+ln(x^2)=1 | | 53-2x=5x | | 11x-10=54 | | 6p^2+25-119=0 | | (6a^3+6a^2-7)+(5a^3-6a+8)= | | 2x^2-45=0 | | y+24y+144= | | 8a+12b+4= | | 9x+12y+15= |

Equations solver categories